Dampak Judi Online terhadap Kondisi Finansial, Hubungan Sosial, dan Prestasi Akademik Mahasiswa: The Impact of Online Gambling on Students' Financial Conditions, Social Relationships, and Academic Performance - Naufal Zaidan Nayottama (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
Online gambling among students has become an increasing concern. This research aims to determine how online gambling affects students' financial, social and academic achievement. This qualitative study seeks to reveal a situation or object in its context and tries to find meaning or in-depth understanding to produce descriptive data. This study uses exploratory research design is used to explore attitudes and reasons for online gambling and its impact on students' lives. The results show that online gambling has a significant negative impact on students' financial, social and academic achievement. Online gambling decreases academic performance due to the buildup of ongoing stress. Furthermore, online gambling affecst students' financial conditions by increasing the costs to play online gambling. The social impact of online gambling changes the students behavior in friendship and family.